Chronic mandibular osteomyelitis with suspected underlying synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome: a case report - Osako T; Kugimoto T; Hirai H; Omura K; Mochizuki Y; Taguchi T (Dove Medical Press, 2012)
Yumi Mochizuki, Ken Omura, Hideaki Hirai, Takuma Kugimoto, Toshimitu Osako, Takahide TaguchiDepartment of Oral and Maxillofacial Surgery, Oral Restitution, Division of Oral Health Sciences, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo, JapanAbstract: Chronic mandibular osteomyelitis is an intractable disease. In recent years, some case reports have related this disease process to synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome, which is chronic with frequent remissions and exacerbations. This report describes a case of chronic mandibular osteomyelitis suspected to be SAPHO syndrome. A 68-year-old woman presented with pain on the left side of the mandible. On the basis of clinical and radiological findings, chronic mandibular diffuse sclerosing osteomyelitis was initially diagnosed. We administrated oral clarithromycin (400 mg daily) and levofloxacin (500 mg daily), and her pain subsequently resolved. On 99mTc-labeled methylene diphosphonate scintigraphy, tracer uptake in the asymptomatic mandible was unchanged, but there was increasing tracer uptake in the sternocostal and sternoclavicular joints, compared with 99mTc-labeled methylene diphosphonate scintigraphic findings of the first visit. We diagnosed SAPHO syndrome and administrated oral sodium risedronate hydrate (2.5 mg daily). Although there has been no pain or swelling in the area of the left mandibular lesion, we have followed up on other skin and osteoarticular manifestations in conjunction with other medical departments.Keywords: SAPHO syndrome, diffuse sclerosing osteomyelitis, 14-membered ring macrolide antibiotics, new quinolone antibiotics, bisphosphonates